Towards an Antarctic spatial data infrastructure : the SCAR King George Island GIS project as a model framework to integrate and redistribute inaccurate and incomplete spatial data - Vogt, Steffen (2005)
The concept of spatial data infrastructures is applied to King George Island, Antarctica. This island is one of the most populated places in Antarctica. Permanent research stations of nine different countries, a runway on ice free ground and major tourism activities have a strong impact on the fragile ecosystems of the island. There is a lack of coordination of activities between the stations and almost no joint environmental management. The Scientific Committee on Antarctic Research has established the King George Island GIS Project to provide an integrated topographic database as a consistent geographic reference for use by all countries and all scientific disciplines and to support environmental management. Using this project as a testbed components required for the emerging Antarctic Spatial Data Infrastructure have been developed and tested. It had to be evaluated if such components could successfully be implemented in the context of a variety of data types and data producers, the broad range of user communities and use cases, and the complex political and institutional framework. If successful in the context of King George Island then these components can be expected to be successful in the wider context of Antarctica The list of components based on ISO TC211 standards and specifications from the OpenGeospatial Consortium includes the SCAR Feature Catalogue for consistent semantics, the identification, definition and construction of framework data sets, an advanced gazetteer that can be used for geolocation services in large scale applications, and geospatial web services for portrayal of and access to geospatial data. In dieser Arbeit wird das Konzept einer Geodateninfrastruktur auf das Management raumbezogener Daten von King George Island, South Shetland Islands, Antarktis angewandt. Dabei wird überprüft, ob sich Komponenten einer Geodateninfrastruktur auch in einem Umfeld bewähren, in dem mit Blick auf die zu verwaltenden raumbezogenen Daten der Umgang mit unvollständigen und ungenauen Daten im ...